2022
DOI: 10.1093/gbe/evac055
|View full text |Cite
|
Sign up to set email alerts
|

What We Talk About When We Talk About “Junk DNA”

Abstract: “Junk DNA” is a popular yet controversial concept that states that organisms carry in their genomes DNA that has no positive impact on their fitness. Nonetheless, biochemical functions have been identified for an increasing fraction of DNA elements traditionally seen as “Junk DNA”. These findings have been interpreted as fundamentally undermining the “Junk DNA” concept. Here, we reinforce previous arguments that this interpretation relies on an inadequate concept of biological function that does not consider t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
(65 reference statements)
0
7
0
2
Order By: Relevance
“…Almost 50% of the human genome is made up of repetitive DNA that does not encode proteins. 50 These DNA sequences are often considered to be "junk DNA" in the human genome. 50 Research has shown that one of the junk DNA sequences, VNTR2-1, actually functions to enhance telomerase gene activity and that the telomerase gene is more active in people with longer VNTR2-1 sequences.…”
Section: Genomic Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 50% of the human genome is made up of repetitive DNA that does not encode proteins. 50 These DNA sequences are often considered to be "junk DNA" in the human genome. 50 Research has shown that one of the junk DNA sequences, VNTR2-1, actually functions to enhance telomerase gene activity and that the telomerase gene is more active in people with longer VNTR2-1 sequences.…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…50 These DNA sequences are often considered to be "junk DNA" in the human genome. 50 Research has shown that one of the junk DNA sequences, VNTR2-1, actually functions to enhance telomerase gene activity and that the telomerase gene is more active in people with longer VNTR2-1 sequences. 51 Notably, however, a shorter sequence does not necessarily mean a shorter lifespan.…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…The complexity and adaptability of biological systems often find their roots in the ever-budding genetic landscape. Central to this is the emergence of de novo genes -- genes that arise from regions of DNA once categorized as ’junk’ and considered functionally insignificant (Fagundes, et al 2022; Ohno 1972). The birth of de novo genes was deemed impossible or functionally irrelevant (Jacob 1977; Mayr 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is that each paralog encodes an N-terminal tail (NTT); so, the resulting NTTs have substantial differences in amino acid sequences [ 51 ], thus maintaining their stoichiometric relationship with partners in multicomponent interactions in changing external conditions [ 48 , 57 ]. As Fagundes et al opine, if a genetic element (the βCENH3 gene in our case) supports the organism’s adaptive level, it is qualified as functional and its “supporting function” is a proper biological function [ 58 ].…”
Section: Gene Duplicationsmentioning
confidence: 99%